2017
DOI: 10.3892/mmr.2017.8148
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial effect of topical ozone on the treatment of MRSA skin infection

Abstract: Skin can be infected by many types of microorganisms, most commonly by gram-positive strains of Staphylococcus and Streptococcus spp. Treatment of Staphylococcus aureus (S. aureus) infections, particularly that of methicillin resistant Staphylococcus aureus (MRSA), is a challenge in clinical practice. Ozone therapy has proven to be one of the strongest antiseptics against the majority of microorganisms involved in skin infections. The purpose of the present study was to evaluate the microbicidal effects of top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 31 publications
1
68
0
10
Order By: Relevance
“…43,44 Recently, clinical trials have been carried out to assess the effect of ozone on chemotherapy-induced oral mucositis. 45,46 Moreover, ozone combined with fluorouracil decreased the resistance of cancer cells to chemotherapy. 47 In our study, it was shown that ozone therapy could effectively attenuate chemotherapeutic enteritis and decrease the blood hypercoagulability in cancer patients (Table 3 and Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Recently, clinical trials have been carried out to assess the effect of ozone on chemotherapy-induced oral mucositis. 45,46 Moreover, ozone combined with fluorouracil decreased the resistance of cancer cells to chemotherapy. 47 In our study, it was shown that ozone therapy could effectively attenuate chemotherapeutic enteritis and decrease the blood hypercoagulability in cancer patients (Table 3 and Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic category includes derivatives (ointment, gel, spray) that can be applied to the skin and to some mucous membranes for dermatological treatment, such as antimicrobials, exudate reducers and wound healing stimulants [15], or for the treatment of acne, herpes, psoriasis, fungal infections, bed sores, and wounds in general [11]. Some in vivo studies have shown that the severe skin lesions that are caused by S. aureus and methicillin-resistant S. aureus (MRSA) have been healed by therapy with ozonated oil in 1-2 months, which prove its great efficacy, limited side effects and low-cost [59]. Indeed, Sechi et al [60] have investigated the antimicrobial activity of ozonated sunflower oil (Oleozon ® ) against pathogens, such as S. aureus, Enterococcus faecalis, E. faecium, S. pyogenes, Escherichia coli, Pseudomonas aeruginosa, and various species of Mycobacterium.…”
Section: Topical Applications Of Ozonated Oilsmentioning
confidence: 99%
“…Bacterial skin infections are widespread all over the world and many are caused by Staphylococcus aureus. The treatment of S. aureus infection, particularly Methicillin-Resistant S. aureus (MRSA), is a challenge in clinical practice (Malachowa et al, 2013;Song et al, 2017).…”
Section: Introductionmentioning
confidence: 99%